1999
DOI: 10.1074/jbc.274.30.20909
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Site-specific DNA Damage Induced by Nitroxyl Anion (NO−) in the Presence of Hydrogen Peroxide

Abstract: Nitroxyl anion (NO ؊ ), the one-electron reduction product of nitric oxide (NO ⅐ ), is formed under various physiological conditions. We have used four different assays (DNA strand breakage, 8-oxo-deoxyguanosine formation in calf thymus DNA, malondialdehyde generation from 2-deoxyribose, and analysis of site-specific DNA damage using 32 P-5-end-labeled DNA fragments of the human p53 tumor suppressor gene and the c-Haras-1 protooncogene) to study the effects of NO ؊ generated from Angeli's salt on DNA damage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 40 publications
1
29
1
1
Order By: Relevance
“…Despite this observation, no increase in apoptosis was detected in cells treated with AS or DEA/NO, indicating that the reduction in cell metabolism by NO could be a reversible process. Although these findings appear to be in contrast with previous reports showing cytotoxicity for NO Ϫ , it needs to be pointed out that in those studies higher concentrations of AS were used (2-5 mM) (63), and exacerbation of cellular damage was observed only when AS was combined with hydrogen peroxide (56). Of interest, and in agreement with results using NO donors (62), we also found that NO Ϫ -mediated HO-1 expression is transient and gradually disappears once the spontaneous generation of NO Ϫ ceases.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Despite this observation, no increase in apoptosis was detected in cells treated with AS or DEA/NO, indicating that the reduction in cell metabolism by NO could be a reversible process. Although these findings appear to be in contrast with previous reports showing cytotoxicity for NO Ϫ , it needs to be pointed out that in those studies higher concentrations of AS were used (2-5 mM) (63), and exacerbation of cellular damage was observed only when AS was combined with hydrogen peroxide (56). Of interest, and in agreement with results using NO donors (62), we also found that NO Ϫ -mediated HO-1 expression is transient and gradually disappears once the spontaneous generation of NO Ϫ ceases.…”
Section: Discussioncontrasting
confidence: 54%
“…The fate of NO Ϫ within the cellular system is unknown, but this unstable species has been reported to react readily with thiols (41,42), and in the presence of molecular oxygen or other oxidants, it can generate other RNS with specific reactivity toward cellular targets (54,55). In the presence of hydrogen peroxide and transition metals, NO Ϫ but not NO appears to cause loss of cell viability by site-specific DNA damage (56). Recent reports using donors of nitroxyl revealed opposite effects by showing either NO Ϫ -mediated exacerbation of post-ischemic myocardial injury (43) or cytoprotection against neuronal damage (57).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of reductants, nitroxides can be readily reduced to the corresponding EPR silent hydroxylamines (32). In support of the latter assumption, the addition of K 3 [Fe(CN) 6 ] to an extract of a reaction solution consisting of 1b, Me 2 SO, and PBN resulted in a pronounced increase of the EPR signal of 4. This effect most likely reflected the oxidation of the EPR silent hydroxylamine 5 to 4 (Scheme 2).…”
Section: Nitroxyl-dependent Generation Of Hydroxyl Radicalmentioning
confidence: 49%
“…When the reaction solution was analyzed by HPLC with electrochemical detection, the predominant formation of 5 was observed (Fig. 3); an addition of K 3 [Fe(CN) 6 ] to the analyzed solutions resulted in the interconversion of the HPLC peaks reflecting the elution of 5 and 4, respectively. The identity of compounds 4 and 5 was confirmed by coinjections of authentic HPLC standards as described previously (32,38).…”
Section: Nitroxyl-dependent Generation Of Hydroxyl Radicalmentioning
confidence: 99%
See 1 more Smart Citation